Exploring essential components of addiction recovery: a qualitative study across assisted and unassisted recovery pathways. (3rd September 2021) - Dekkers, Anne; Bellaert, Lore; Meulewaeter, Florien; De Ruysscher, Clara; Vanderplasschen, Wouter
Abstract: Even though various pathways to addiction recovery have been identified, knowledge on overarching essential components of addiction recovery processes remains limited. To explore these essential components, in-depth interviews were conducted with a heterogeneous group of individuals across pathways to addiction recovery (i.e. a low-threshold activation center, Narcotics Anonymous, a CRA + vouchers out-patient program, residential treatment programs, and 'natural' recovery). The interviews ( n  = 25) were audio-taped, transcribed verbatim, and thematically analyzed. In-depth analysis of the data resulted in a model that includes essential components of addiction recovery processes and their dynamic relationship. 'Time' and 'supportive environments' were identified as the foundations and facilitators for the transformative changes required in addiction recovery processes, which in turn contributed to 'developing a sense of self' and 'developing a sense of future'. These components, interrelated and in a continuous interplay with each other, facilitated recovery processes. As a result, recovery-oriented support should be strengthened and specifically focus on supporting these essential components, by providing tailor-made and continuously available support. Given the relational character of addiction recovery processes, social networks and society at large should evolve towards the development of responsive and inclusive spaces to support persons in addiction recovery.